Electroencephalogram abnormalities in full term infants with history of severe asphyxia - Susanti Halim; I Gusti Nyoman Made Suwarba; I Made Kardana (Indonesian Pediatric Society, 2015)
Background An electroencephalogram (EEG) is an electroimaging tool used to determine developmental and electrical problems in the brain. A history of severe asphyxia is a risk factor for these brain problems in infants. Objective To evaluate the prevalence of abnormal EEGs in full term neonates and to assess for an association with severe asphyxia, hypoxic ischemic encephalopathy (HIE), and spontaneous delivery. Methods This cross-sectional study was conducted at the Pediatric Outpatient Department of Sanglah Hospital, Denpasar, from November 2013 to January 2014. Subjects were fullterm infants aged 1 month who were delivered and/or hospitalized at Sanglah Hospital. All subjects underwent EEG. The EEGs were interpreted by a pediatric neurology consultant, twice, with a week interval between readings. Clinical data were obtained from medical records. Association between abnormal ECG and severe asphyxia were analyzed by Chi-square and multivariable logistic analyses. Results Of 55 subjects, 27 had a history of severe asphyxia and 28 were vigorous babies. Forty percent (22/55) of subjects had abnormal EEG findings, 19/22 of these subjects having history of severe asphyxia, 15/22 had history of hypoxic-ischemic encephalopathy (HIE), and 20/22 were delievered vaginally. There were strong correlations between the prevalence of abnormal EEG and history of severe asphyxia, HIE, and spontaneous delivery. Conclusion Prevalence of abnormal EEG among full-term neonates referred to neurology/growth development clinic is around 40%, with most of them having a history of severe asphyxia. Abnormal EEG is significantly associated to severe asphyxia, HIE, and spontaneous delivery.